2023
DOI: 10.3390/electronics12204323
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review on Multiple Instance Learning

Samman Fatima,
Sikandar Ali,
Hee-Cheol Kim

Abstract: Multiple-instance learning has become popular over recent years due to its use in some special scenarios. It is basically a type of weakly supervised learning where the learning dataset contains bags of instances instead of a single feature vector. Each bag is associated with a single label. This type of learning is flexible and a natural fit for multiple real-world problems. MIL has been employed to deal with a number of challenges, including object detection and identification tasks, content-based image retr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(2 citation statements)
references
References 78 publications
0
2
0
Order By: Relevance
“…Other mentioned methods are extensions or adaptations of conventional ones applicable to single‐instance learning. Comprehensive reviews of the MIL concept and its applications in regular ML tasks can be found in reviews 9–11,38,45–49 …”
Section: Origins Of Multi‐instance Learningmentioning
confidence: 99%
See 1 more Smart Citation
“…Other mentioned methods are extensions or adaptations of conventional ones applicable to single‐instance learning. Comprehensive reviews of the MIL concept and its applications in regular ML tasks can be found in reviews 9–11,38,45–49 …”
Section: Origins Of Multi‐instance Learningmentioning
confidence: 99%
“…Comprehensive reviews of the MIL concept and its applications in regular ML tasks can be found in reviews. [9][10][11]38,[45][46][47][48][49]…”
Section: Origins Of Multi-instance Learningmentioning
confidence: 99%